Pelatihan Implementasi Chatbot Sistem Informasi Layanan Pelanggan CV. Mockerz Apparel - Disa, Syaharullah; Tamsir, Tamsir; Khadafi, Farid Rahmat; Mahsud, Mahsud; Sabir, Fitriana M; Arifin, Rohayati Rahmat (LESTARI : Jurnal Pengabdian Kepada Masyarakat, 2024)
CV. Mockerz Apparel Industries is a plain t-shirt specialist experienced since 2012, continues to grow and produce quality products to meet customer needs. The current problem is related to customer information services. Lack of media to disseminate product-related information can reduce customer reach. With the available technology, it is possible to implement a system that can help disseminate information to make it easier for customers to obtain product-related information. By looking at the existing conditions and realities, the author implemented and provided training on the Chatbot customer service information system to solve the problems described earlier. The system was developed using the DevOps (development and operations) method, including several phases: plan, develop, build, test, operate, and monitor). Implementation activities used tutorial methods and technical assistance. The activity was successful, and CV Mockerz Apparel staff as partners also participated until the end of the activity. The partner's perception of the community service activity was beneficial because the chatbot system developed was very suitable for them to implement.